Drug disposing behavior and awareness of the concept of ecopharmacovigilance among the medical faculty - Praveen, Shubha; Amol, Gramle; Reddy, Shivakumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The ever-increasing impact of drugs on the environment has added an altogether new dimension of monitoring, assessing and documenting the known and unknown drug effects on our fragile environment in the form of ecopharmacovigilance. This study was carried out to document the drug disposing behavior and awareness of the concept of ecopharmacovigilance among the medical faculty of a tertiary care Medical Hospital. Methods: A detailed, structured, anonymous questionnaire consisting of both open and close ended essential queries on drug disposal practices was prepared and response obtained from the participants which included an agglomeration of teaching faculty and the clinicians of various disciplines of the Institute. Results: 97.87% of the participants obtained drugs in excess which included a majority of solid (68.12%) and liquid (31.88%) dosage forms. The maximum medicines obtained in excess included analgesics and antipyretics (89.36%), anti-asthmatics (15.22%), and anti-emetics (13.48%). 82.8% of the respondents were unaware of the proper drug disposal technique and 94.7 % of the respondents practiced open disposal of the drugs. Conclusions: An abysmally low level of awareness about ecopharmacovigilance and unhealthy, irrational method of drug disposal was documented in our study. Appropriate training of those who handle drugs in hospitals and healthcare establishments is the need of the hour.